Feasibility and Sensitivity Analysis of the Banana Bolen Agroindustry at CV Mayang Sari Bandar Lampung - Fadilah Nur Safitri; Dwi Haryono; Fembriarti Erry Prasmatiwi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
A high initial investment requirement, high operating costs, and variations in raw material pricing and market demand are just a few of the difficulties CV Mayang Sari faces. Furthermore, the COVID-19 pandemic and competition in urban areas have impacted production methods and profitability. This study aims to assess the sensitivity and financial viability of the banana bolen enterprise run by CV Mayang Sari in Bandar Lampung City. The study used a case study methodology and was carried out from August to September 2024 at CV Mayang Sari, Bandar Lampung, a purposefully chosen locale. The owner and staff were among the respondents in this survey, and they supplied important details about the operational and financial facets of the company. Primary data from 2016 was used. The information utilized included secondary data gleaned from relevant documents and records, and primary data gathered through in-person interviews between 2016 and 2024. Data analysis used financial feasibility indicators, including a positive NPV, IRR exceeding the 10% discount rate, Gross B/C greater than 1, Net B/C greater than 1, and a Payback Period of less than 10 years. The findings demonstrated that CV Mayang Sari's business is both profitable and financially feasible, with an NPV of Rp 194,340,766, a payback period of 7 years and 2 months, a Gross B/C of 1.13, a Net B/C of 3.17, and an IRR of 41%. Furthermore, based on sensitivity analysis, the business remains feasible under various changes, such as a 16% decrease in banana bolen sales, 11% in unsold products, and a 24.79% increase in plantain prices.